Tourist perceptions and expectations towards the quality breakfast at harris cafe - Putra, I Putu Suyasa; Ariani, Ni Made; Suarka, Fanny Maharani (Jurnal Kepariwisataan dan Hospitalitas, 2019)
Hotel are one of the industries that are engaged in food and beverage service, and facilities for sleeping to tourists. Harris Hotel Raya Kuta is four star hotels located on Jalan Raya Kuta 83E, Kuta, Badung. Food and beverages service are the second income of the hotel after the sale of rooms, therefore in its operation it needs special attention so that the standards can run smoothly. There are several complaints from tourists who have done breakfast makes the need for improvements to some things related to the quality of the breakfast.Data collection techniques were observation, interviews, documentation, questionnaires, and literature studies. The sampling technique using quota sampling with the Slovin formula obtained 100 respondents and used accidental sampling when distributing questionnaires. The data analysis technique uses qualitative analysis and quantitative analysis in the form of descriptive statistics with likert analysis with a score scale of 1 - 4 and importance level analysis.Based on the importance level diagram analysis, there are several things to consider, namely Quadrant A, namely the taste of food and the shape of the pieces. Quadrant B is food composition and freshness of food. Quadrant C is food texture, food temperature, and food maturity level. Quadrant D is the appearance, aroma, and color of the combination of ingredients. Based on the overall level of conformity the results of the calculation of the level of conformity are categorized as satisfied.The Food and Beverage Department at Harris Hotel Raya Kuta in terms of food taste, variations in the shape of pieces, and maturity level need to be improved and improved because the three indicators are in the top priority in terms of quality.